1984
DOI: 10.1007/bf00743244
|View full text |Cite
|
Sign up to set email alerts
|

The oligomycin sensitivity conferring protein (OSCP) of beef heart mitochondria: Studies of its binding to F1 and its function

Abstract: The binding of "oligomycin sensitivity conferring protein" (OSCP) to soluble beef-heart mitochondrial ATPase (F1) has been investigated. OSCP forms a stable complex with F1, and the F1 X OSCP complex is capable of restoring oligomycin- and DCCD-sensitive ATPase activity to F1- and OSCP-depleted submitochondrial particles. The F1 X OSCP complex retains 50% of its ATPase activity upon cold exposure while free F1 is inactivated by 90% or more. Both free F1 and the F1 X OSCP complex release upon cold exposure a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It was, however, not efficiently associated with the subunits constituting the stalk linking F1 to F0 since the ATPase activity was cold-labile. Indeed, it has been shown in beef heart F1 that the binding of isolated F1 to OSCP (30,12) or to other subunits constituting the stalk such as subunits b, F6, and d (12) decreases F1 sensitivity to cold exposure. Therefore, the cold-sensitivity of the F1-ATPase in human °cells indicates that at least some of the stalk subunits are deficient.…”
Section: Discussionmentioning
confidence: 99%
“…It was, however, not efficiently associated with the subunits constituting the stalk linking F1 to F0 since the ATPase activity was cold-labile. Indeed, it has been shown in beef heart F1 that the binding of isolated F1 to OSCP (30,12) or to other subunits constituting the stalk such as subunits b, F6, and d (12) decreases F1 sensitivity to cold exposure. Therefore, the cold-sensitivity of the F1-ATPase in human °cells indicates that at least some of the stalk subunits are deficient.…”
Section: Discussionmentioning
confidence: 99%
“…FI affords some protection against trypsin proteolysis of either the b-subunit of E. coli (Hermolin et al, 1983;Perlin et al, 1983;Hoppe et al, 1983) or OSCP (Hundal et al, 1984). The trypsin cleavable segment of the b-subunit is not required for proton translocation through F0 (Hermolin et al, 1983;Perlin et al, 1983;Hoppe et al, 1983) although the b-subunit is compulsory for the reconstitution of proton translocation (Schneider & Altendorf, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…These results were corroborated and expanded by other authors, who showed that CypD deficiency attenuated ATP synthase dysregulation, restoring bioenergetics, via interaction with the oligomycin-sensitivity conferring protein (OSCP) [ 76 , 78 ]. OSCP is a protein that is located in the peripheral stalk of the ATP synthase, providing structural stability to this enzyme [ 86 ]. While the expression of OSCP has been demonstrated to decrease with aging, the interaction between CypD and OSCP increases with aging, most likely due to the increased expression of CypD [ 77 , 78 ].…”
Section: Atp Synthase Dysfunction In Admentioning
confidence: 99%